ANALYSIS WITH RTI (REFLECTANCE IMAGING TRANSFORMATION) IN TWO SITES OF PERU WITH QUILCAS: TECHNOLOGY, DETERIOTATION AND CONSERVATION - Echevarría, Gori Tumi (2014)
Having completed two field seasons using the computational photography technique called Reflectance Transformation Imaging (RTI) in the study of quilcas or rock art sites in Peru, the authors have been able to consider and analyze important information which is usually overlooked in the study of this material, such as the manufacturing techniques used and the state of conservation of rock art panels. This allowed the authors to propose new methodological standards for the documentation of rock art and consider new approaches for its scientific study.Using RTI as part of the documentation process, the present article compares two rock art sites, Checta and X02, in the central coast and the south coast respectively. The results of this comparative analysis, which included a sample from each site, demonstrate that RTI is a useful tool for the scientific investigation of rock art in Peru, regardless of the type of rock used as support or the region in which the rock art sites are located. The results also allow the authors to evaluate the integrity of the aforementioned rock art sites, considering issues of conservation and preservation, therefore incorporating this type of technical analysis into future studies of this material.